Ambiente de aprendizaje y su incidencia en el desarrollo cognitivo de los estudiantes del segundo año de la Unidad Educativa Adolfo María Astudillo, 2023 - Minda Vasquez, Victor Manuel (2023)
This project will focus its study on the learning environments with which we work at the basic education level, being this stage of great importance for the integral development of infants. The basic education curriculum states that child development is integral and includes all its components (cognitive, social, psychomotor, physical and affective), which are connected and occur in natural and cultural environments. It is necessary to promote learning opportunities and encourage exploration in diverse and rich environments, full of affection, warmth and interactions to ensure this holistic approach. The problem lies in the way in which learning environments affect the cognitive development of students in the second year of the Adolfo María Astudillo educational unit. As a result of the surveys to teachers, it was identified that there is knowledge about the management of learning environments, however, there is a low percentage of lack of knowledge and management due to the lack of information and training about them. It is important that the institutions can provide, support and promote the knowledge of teachers in order to provide an effective and quality education. The play-work spaces will allow children to learn spontaneously according to their needs, improving the relationship between the subject and the environment in which he/she lives, both for his/her educational well-being and throughout his/her life. By developing their social and cognitive skills, children will be able to solve problems that affect the whole educational community and develop a specific solution strategy that suits the learner's well-being.